Comparison of patients’ acceptance of cuff-based vs wearable 24-hour ambulatory blood pressure monitoring devices: A multi-method study - Ariffin Kawaja; Aminath Shiwaza Moosa; Eric Kam Pui Lee; Ian Kwong Yun Phoon; Andrew Teck Wee Ang; Zi Ying Chang; Aileen Chelsea Ai’En Lim; Jonathan Yap; Weiting Huang; Ding Xuan Ng; Melvin Yuansheng Sng; Hao Yuan Loh; et al. (PLoS ONE, 2025)
Introduction Recent hypertension guidelines recommend ambulatory blood pressure monitoring (ABPM) for accurate diagnosis and monitoring. However, patients’ experiences with cuff and wearable ABPM devices in primary care remain unclear. This study compared the acceptance of three devices (oscillometry cuff, tonometry wrist, and photoplethysmography chest devices) among patients with hypertension in primary care. Methods A multi-method study was conducted. Thirty-five participants with hypertension were recruited from two public primary care clinics in Singapore. All participants used cuff-based and either wrist or chest wearable devices for 24 hours. Structured surveys and in-depth audio-recorded interviews were used to gather feedback on their views, experiences, and challenges using the devices. The interviews were thematically analysed, and the surveys were analysed using descriptive statistics. Results All participants used the cuff (n = 35) device, while the wrist and chest devices were used by two-thirds (n = 22) and a third (n = 11) of the participants, respectively. The device usability questionnaire found that most participants were satisfied with the chest device, which did not disrupt their daily activities. Conversely, cuff arm devices interfered with daily activities (48%) and sleep (26%), were cumbersome (32%), and caused embarrassment (26%). The wrist device was uncomfortable (33%) and painful (22%) for some participants. The qualitative data were categorised into five themes: comfort, convenience, perceived accuracy, and impact on routine and sleep. Participants found the chest device more comfortable and convenient than the cuff and wrist devices. The cuff device was perceived as the most accurate due to its inflation-based BP measurement. All devices minimally affected routines and sleep, though participants expressed safety concerns about the cuff device, particularly while driving. Conclusion While wearable ABPM devices offer increased comfort, convenience and reduced impact on patient’s daily activities, concerns regarding their accuracy must be addressed before the widespread adoption of these devices in routine clinical practice.